2011
DOI: 10.1016/j.cellsig.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

TRIP6: An adaptor protein that regulates cell motility, antiapoptotic signaling and transcriptional activity

Abstract: Thyroid hormone receptor interacting protein 6 (TRIP6), also known as zyxin-related protein-1 (ZRP-1), is an adaptor protein that belongs to the zyxin family of LIM proteins. TRIP6 is primarily localized in the cytosol or focal adhesion plaques, and may associate with the actin cytoskeleton. Additionally, it is capable of shuttling to the nucleus to serve as a transcriptional coregulator. Structural and functional analyses have revealed that through multidomain-mediated protein-protein interactions, TRIP6 serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 52 publications
2
49
0
Order By: Relevance
“…As such, it is not surprising that these LIM proteins, in particular TRIP6 and LPP, share some of the same binding partners (1). Indeed, the in vitro GST pulldown assays showed that LPP, but not zyxin, also bound to both p27 KIP1 and AKT1 directly albeit with a lower affinity than TRIP6 (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As such, it is not surprising that these LIM proteins, in particular TRIP6 and LPP, share some of the same binding partners (1). Indeed, the in vitro GST pulldown assays showed that LPP, but not zyxin, also bound to both p27 KIP1 and AKT1 directly albeit with a lower affinity than TRIP6 (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…hyroid hormone receptor-interacting protein 6 (TRIP6) is a zyxin-related adaptor protein and focal adhesion molecule (1). Through its three LIM domains, PDZ-binding motif, Crk SH2-binding motif, and several putative SH3-binding domains, TRIP6 associates with a variety of molecules from the cell surface to the nucleus to regulate actin reorganization, focal adhesion assembly/disassembly, cell migration/invasion, antiapoptotic signaling, and transcriptional control.…”
mentioning
confidence: 99%
“…Thyroid hormone receptor-interacting protein 6 (TRIP6) is a zyxin-related adaptor protein and focal adhesion molecule (28). TRIP6 associates with a variety of molecules from the cell surface to the nucleus, regulates actin reorganization, focal adhesion assembly/disassembly, cell migration/invasion, antiapoptotic signaling, and transcriptional control.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone receptor-interacting protein 6 (TRIP6), a LIM proteins family member, is an adaptor protein that mediates many cell responses, such as actin cytoskeletal reorganization and cell adhesion [7]. Accumulating data suggest that TRIP6 can exert a critical role in cancer progression.…”
Section: Introductionmentioning
confidence: 99%